2020
DOI: 10.1038/s41598-020-66722-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of robot-assisted pancreaticoduodenectomy during initial learning curve versus laparotomy

Abstract: to analyze the initial learning curve (Lc) for robot-assisted pancreaticoduodenectomy (RApD) and compare RApD during the initial Lc with open pancreaticoduodenectomy (opD) in terms of outcome. this study is a retrospective review of patients who consecutively underwent RApD and opD between October 2015 and January 2020 in our hospital. 41 consecutive RAPD cases and 53 consecutive open cases were enrolled for review. Compared with OPD, RAPD required a significantly longer operative time (401.1 ± 127.5 vs. 230.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…No one else has done similar research in RPD before. The operation time, intraoperative blood loss, conversion to laparotomy rate, and complications (Clavien–Dindo grade ≥ 3) in this study are similar to those reported in other single-center or multicenter reports ( 32 , 42 , 43 ), so our DSS-Han for the RPD system may also be comparable in other institutions. We first discover and propose the concept of mesenteric tissue thickness (P1) in clinical practice.…”
Section: Discussionsupporting
confidence: 86%
“…No one else has done similar research in RPD before. The operation time, intraoperative blood loss, conversion to laparotomy rate, and complications (Clavien–Dindo grade ≥ 3) in this study are similar to those reported in other single-center or multicenter reports ( 32 , 42 , 43 ), so our DSS-Han for the RPD system may also be comparable in other institutions. We first discover and propose the concept of mesenteric tissue thickness (P1) in clinical practice.…”
Section: Discussionsupporting
confidence: 86%
“…Either laparoscopic or robotic NOSES could be performed in our department 24 , 25 . As per our experience, especially in ultra-low rectal cancer, robotic NOSES has advantage compared with laparoscopic NOSES.…”
Section: Discussionmentioning
confidence: 99%
“…However, providing a specific number of procedures to be an independent assistant and operator would be cumbersome because the learning curve may be affected by several factors, including previous experiences in pancreatic surgery and minimally invasive surgery. The learning curve for RPD has been reported to be different from approximately 30 to 80 cases [ 13 16 ]. Therefore, at least 30 cases may be required to become an independent assistant or operator.…”
Section: Resultsmentioning
confidence: 99%